Development of Practicum Assessment Rubric Assisted by Google Spreadsheet in Basics Electronics Material - Muh. Syihab Ikbal; Belinda Dwi Utami; Andi Halimah (Universitas Lambung Mangkurat, 2023)
The implementation of practicum assessment rubrics in the Physics Education Laboratory of UIN Alauddin Makassar has fallen short of its full potential. Thus, it is critical to develop a standardized rubric. The practicum assessment rubric is utilized to assess the proficiency of students during their practicum. This research aims to (1) describe the procedure for developing a practicum implementation assessment rubric for Basic Electronics courses with the assistance of the Google Spreadsheet application; and (2) describe the quality of the practicum implementation assessment rubric based on validity and practicality for Basic Electronics courses with the assistance of the Google Spreadsheet application. The utilized development model is Tessmer's formative research model, which comprises two stages: preliminary and formative evaluation. The formative evaluation stage incorporates self-evaluation, prototyping (including expert reviews, one-on-one, and small group), and a field test. This research was conducted at the Physics Education Laboratory of UIN Alauddin Makassar. The research subject comprised two individuals: the main subject and the trial test subject. The main subject comprised two individuals who subsequently formed the product validator team. The trial test subject comprised seven individuals who were employed as assistants for the Electronics practicum in 2022/23. The research results indicated that the validity of the developed product is deemed valid with the validity value of 1. Based on the practicality analysis results, which indicated that 29% of users provided practical responses and 71% provided very practical responses regarding the developed products, it can be inferred that the developed assessment rubric satisfied the practicality criteria. The results of this study suggest that the developed assessment rubric facilitates the assessment administered by the practicum assistants. Additionally, the developed assessment rubric is applicable to all practicum titles pertaining to Basic Electronics.